Structure-related inhibitory effect of antimicrobial enoxacin and derivatives on theophylline metabolism by rat liver microsomes. - Mizuki, Y (1996)
Enoxacin, an antimicrobial fluoroquinolone with a 7-piperazinyl-1, 8-naphthyridine skeleton, is a potent inhibitor of cytochrome P-450-mediated theophylline metabolism. The present study was designed to clarify, using seven enoxacin derivatives, the molecular characteristics of the fluoroquinolone responsible for the inhibition. Three derivatives with methyl-substituted 7-piperazine rings inhibited rat liver microsomal theophylline metabolism to 1,3-dimethyluric acid to an extent similar to that of enoxacin (50% inhibitory concentrations [IC50s] = 0.39 to 0.48 mM). 7-Piperazinyl-quinoline derivatives, 8-hydroenoxacin (8-Hy) and 1-cyclopropyl-8-fluoroenoxacin (8-F1), which have a hydrogen and a fluorine at position 8, respectively, more weakly inhibited metabolite formation (IC50s = 0.88 and 1.29 mM, respectively). Little inhibition (IC50 > 2 mM) was observed in those with 3'-carbonyl and 4'-N-acetyl groups on the piperazine rings. The substrate-induced difference spectra demonstrated that the affinities of enoxacin, 8-Hy, and 8-F1 to cytochrome P-450 were parallel with their inhibitory activities. The substituent at position 8 was found to determine the molecular conformations of the fluoroquinolones, and the planarity in molecular shape decreased in the same order as the inhibitory activity (enoxacin > 8-Hy > 8-F1). Moreover, the 3'-carbonyl and 4'-N-acetyl groups decreased the basicity of their vicinal 4'-nitrogen atoms when judged from their electrostatic potentials, which showed a remarkably broadened negative charge around the nitrogens. As a result, the planarity of the whole molecule and the basicity of the 4'-nitrogen atom of enoxacin are likely to be dominant factors in the inhibition of theophylline metabolism by cytochrome P-450.